1994
DOI: 10.1017/s0021932000021180
|View full text |Cite
|
Sign up to set email alerts
|

Breast-feeding and child survival in Matlab, Bangladesh

Abstract: This study investigates the effect of both total and unsupplemented breast-feeding in conjunction with birth interval on early childhood mortality, using longitudinal data from Matlab, Bangladesh. A discrete hazard model approach shows that it is not the duration of total breast-feeding but the duration of unsupplemented breast-feeding which increases child survival. Unsupplemented breast-feeding appears as such a crucial determinant of early childhood mortality that its effect could not be substantially atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A study conducted in Kenya showed that children who were breastfed for more than 6 months have significantly lower probability ( < 0.05) of mortality compared to children breastfed for less than 6 months [10]. Also, in Bangladesh, a study revealed that the duration of breastfeeding was an important determinant of childhood mortality [19]. This may be due to the fact that antimicrobial and anti-inflammatory factors in breast milk provide protection from infection.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Kenya showed that children who were breastfed for more than 6 months have significantly lower probability ( < 0.05) of mortality compared to children breastfed for less than 6 months [10]. Also, in Bangladesh, a study revealed that the duration of breastfeeding was an important determinant of childhood mortality [19]. This may be due to the fact that antimicrobial and anti-inflammatory factors in breast milk provide protection from infection.…”
Section: Discussionmentioning
confidence: 99%
“…The early age at weaning suggests that ancestral humans evolved an unusual capacity to reduce the length of exclusive and transitional feeding without increasing mortality. In humans, an inverse relationship between birth interval and child survival is mediated by breastfeeding (149,209,236). Birth intervals below two years are risky for older sibs.…”
Section: Demographic Implicationsmentioning
confidence: 99%
“…T here is ample evidence of a positive influence of breastfeeding, especially exclusive breastfeeding, on the survival of the child [1][2][3][4][5] but less information regarding effects on cause-specific mortality, such as that attributable to acute respiratory infections (ARI) and diarrhea. Yoon et al 6 reported a higher risk of diarrhea mortality associated with not breastfeeding, whereas the risk for death attributable to ARI, although higher, was not statistically significant.…”
mentioning
confidence: 99%